Sistem Presensi Pegawai Berbasis Website dengan Geolokasi, Swafoto, dan Deteksi Otomatis Ketidakhadiran (Alpa) di Kantor Bapperida Provinsi Papua Tengah - Ester Ayuk Pusvita; Arkiles Sakarias Kamodi (Jurnal Teknologi dan Informatika, 2026)
The main goal of developing a Website-Based Employee Attendance System with the integration of geolocation and selfies at the Central Papua Provincial Bapperida Office is to improve the accuracy and efficiency of recording employee attendance. This system is designed to verify the identity and location of employees in real-time, thereby reducing the potential for fraud while increasing the transparency of attendance data. The website developed has a simple and easy-to-use interface, allowing each employee to make a presence quickly and practically. This study reviews the latest attendance management technology with a focus on security, reliability, and ease of use. The results of the study show that a web-based attendance system with geolocation and selfie support can optimize time and resources, as well as support more accurate and integrated attendance data management. Thus, this system is expected to be a strategic solution in improving the quality of employee attendance management at the Central Papua Provincial Bapperida Office, as well as strengthening transparency and accountability in government administration governance.